2017
DOI: 10.1186/s12931-017-0628-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycopyrronium and indacaterol, as monotherapy and in combination, on the methacholine dose-response curve of mild asthmatics: a randomized three-way crossover study

Abstract: Background: Methacholine dose-response curves illustrate pharmacologic bronchoprotection against methacholineinduced airway hyperresponsiveness and can be used to quantitate changes in airway sensitivity (position), reactivity (slope), and maximal responsiveness following drug administration. Our objective was to determine the influence of single-dose glycopyrronium (long-acting muscarinic antagonist) and indacaterol (ultra-long acting β 2 agonist), as monotherapy and in combination, on the methacholine dose-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…40 Blais et al showed the bronchoprotective effect of GLY in asthmatic patients. 41 Virchow and their colleagues also showed the beneficial effect of GLY on ICS/LABA in uncontrolled asthma. 42 The BUD administered in this study is an ICS retained in airway tissue for longer than other inhaled steroids, resulting in significant prolongation of the anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 95%
“…40 Blais et al showed the bronchoprotective effect of GLY in asthmatic patients. 41 Virchow and their colleagues also showed the beneficial effect of GLY on ICS/LABA in uncontrolled asthma. 42 The BUD administered in this study is an ICS retained in airway tissue for longer than other inhaled steroids, resulting in significant prolongation of the anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have addressed the effect of beta 2 agonists on other aspects of the methacholine dose–response curve. 22 , 39 , 40 All three studies confirm that beta agonists do not lead to a methacholine dose–response plateau, and that they may actually increase the steepness of the dose–reponse curve (ie, reactivity). 39 …”
Section: Bronchodilatorsmentioning
confidence: 76%
“…Glycopyrronium bronchoprotection at 1, 24, and 48 hours was reproduced by this same group in a subsequent study. 22 Neither treatment produced clinically significant bronchodilation, possibly explained by the mild asthma study population.…”
Section: Bronchodilatorsmentioning
confidence: 93%
See 1 more Smart Citation
“…This was a retrospective analysis of additional data from a previous study [4] that examined the influence of respiratory medications on the MDRC of mild asthmatics for comparison with a control non-asthmatic MDRC [approved by institution Research Ethics Board (Bio-REB 16-205) and registered on clinicaltrials.gov (NCT02953041)]. During data collection, it was found that a significant number of control participants were in fact hyperresponsive to methacholine.…”
mentioning
confidence: 99%